Clinical applications of proton MR spectroscopy in the diagnosis of brain tumours. Issue 2 (2004) - Bulakbasi Bulakbasi, Nail Nail
Abstract : There are few but important problems in magnetic resonance (MR) diagnosis of the brain tumours such as predicting the grade, exact definition of the tumour borders, differentiation of the cystic tumours from abscess, the tumoral core from peritumoral oedema, and the tumour recurrence from radiation necrosis. MR spectroscopy (MRS) can add more information to MR imaging (MRI) in solving many of these problems. Widespread usage of faster MRS applications with higher signal‒to‒noise ratio (SNR) and spatial resolution, allows us to detect functional metabolic changes, which provides more data to understand the exact nature of the tumour and the morphological and physiological changes occurring in the surrounding brain parenchyma.